Urinary Tract Infections in Children: Changing Trends in Etiology and Local Resistance Patterns over a Three-Year Period - Patrícia Sousa; Lucinda Delgado; Susana Correia-de-Oliveira; Cecília Pereira; Ângela Dias; Ana Cláudia Tavares (Acta Médica Portuguesa)
Introduction: Urinary tract infections are common in pediatrics. Knowledge of local resistance patterns is crucial to guide empirical antibiotic therapy. We aimed to review the pathogens implicated in urinary tract infections, local resistance patterns, and the impact of switching first-line empirical antibiotic regimens. Methods: We conducted a cross-sectional study including pediatric patients performing urine cultures in a hospital in northern Portugal over two periods: 2019 (group 1) and 2022 (group 2). Between time periods, an internal guideline was implemented recommending cefuroxime as the first-line choice for empirical treatment of urinary tract infections, according to local resistance patterns. Uropathogens, empirical antibiotic choices and resistance patterns were compared among groups. Results: The final sample included 402 cases of urinary tract infections in group 1 and 398 in group 2. Escherichia coli was the most common uropathogen (79.4 - 83.3%), followed by Proteus mirabilis and Klebsiella spp. The most common empirical antibiotic in group 1 was amoxicillin-clavulanate (A-C), as opposed to cefuroxime in group 2 (p < 0.001). The most common resistance was to ampicillin (39.3% - 39.7%). Resistance to A-C slightly decreased (33.1% vs 27.4%, p = 0.079), while resistance to cefuroxime (4.7% vs 3.3%, p = 0.292) and trimethoprim-sulfamethoxazole (TMP-SMX) remained similar (15.2% vs 14.1%, p = 0.659). Resistances to nitrofurantoin (9.0% vs 0.3%, p < 0.001) and fosfomycin (1.7% vs 0.3%, p < 0.036) significantly decreased from group 1 to group 2. Conclusion: E.coli remains the predominant pathogen in pediatric urinary tract infections. Resistance to A-C in our sample was high (33.1%). The switch from A-C to cefuroxime as first-line agent resulted in a decreasing trend in A-C resistance, while cefuroxime resistance remained low and even slightly lower.